Implementasi Program Perlindungan Perempuan Korban Kekerasan Dalam Rumah Tangga di Kota Semarang (Studi pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak) - Beladina Yunia Satriani; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
The women's protection program from acts of violence is one of the steps taken by the Semarang city government to prevent, facilitate, and take in hand with victims of violence in order to get services related to the violence they experienced. The implementation of protection is divided by the stages of preventing acts of violence, protection from acts of violence, recovery, and coordination. The protection services provided by the Semarang City Government are complaints handling, medical services, psychological services and rehabilitation, legal assistance and social reintegration. This policy was set by the Semarang City Government, which then appointed the office of Women's Empowerment and Child Protection, which was assisted by a technical implementation unit to reduce the number of violence, especially domestic violence against women, which was increasing every year. This research is a descriptive qualitative research that aims to find out and analyze the process of policy implementation and inhibiting factors. The theory used in this study is according to Usman, which states that implementation is geared towards activities, actions, actions, or the existence of a system mechanism. Implementation is not just an activity, but a planned activity and to achieve the objectives of the activity. The results showed that the presence of services and technical implementation units, cases of violence against women can be known by the number of complaints that came in, but in the implementation of policies still hampered by several things such as lack of commitment and communication between members, lack of availability of human, financial and facilities resources. It can be concluded that the implementation of the policy of protecting women from acts of violence, especially in the household in facilitating the protection of women from acts of violence has not had a significant impact on the people of Semarang City considering that domestic violence is still high and increasing every year.Keywords: Implementation, violence against women, domestic violence, inhibiting factors.